An Analysis of English Beauty Terms in the Impressions of YouTube by Beauty Vlogger: An Analysis of English Beauty Terms in the Impressions of YouTube by Beauty Vlogger - Nike Puspita Wanodyatama Nike (English Journal Literacy Utama, 2022)
The title of this research is “An Analysis of English Beauty Terms in the Impressions of YouTube by Beauty Vlogger.” The writer takes data from the YouTube channel of Suhay Salim in https://www.youtube.com/user/suhay12/featured on March 11, 2019, at 7.18 p.m. The writer uses qualitative method and browsing the internet for data analysis technique. The identification of the problems are searching the kinds of part of speech of English beauty terms, searching the amount of English beauty terms and searching the meanings of English beauty terms. This research has purposes to classify kinds of part of speech of English beauty terms, to find out the number of English beauty terms and to understand the meanings of English beauty terms. From the data analysis, the writer found that were 6 data (100.0%) English beauty terms in 4 videos of Suhay Salim’s YouTube Channel, which is divided into four functions as follows: Nouns in this research can be recognized by their endings (-ence and -er) e.g. essence and bronzer (33.33%). Adjectives can be recognized by ending (-y) e.g. glossy and greasy (33.33%). Verb in this research can be recognized by ending (-ing) e.g. creasing (16.67%) and Adverb can be recognized by the name of place e.g. Watson (16.67%). The meanings of English beauty terms that are found in this research are denotative meanings. Keywords: Part of Speech, Meanings, Beauty, YouTube, Suhay Salim.